The emerging roles and therapeutic potential of B cells in sepsis - Ma, Chengyong; Liu, Hanrui; Yang, Shuo; Li, Hong; Liao, Xuelian; Kang, Yan (Frontiers in Pharmacology, 2022)
Sepsis is a life-threatening syndrome caused by anomalous host response to infection. The pathogenesis of sepsis is complex, and immune dysfunction is the central link in its occurrence and development. The sepsis immune response is not a local and transient process but a complex and continuous process involving all major cell types of innate and adaptive immunity. B cells are traditionally studied for their ability to produce antibodies in the context of mediating humoral immunity. However, over the past few years, B cells have been increasingly recognized as key modulators of adaptive and innate immunity, and they can participate in immune responses by presenting antigens, producing cytokines, and modulating other immune cells. Recently, increasing evidence links B-cell dysfunction to mechanisms of immune derangement in sepsis, which has drawn attention to the powerful properties of this unique immune cell type in sepsis. Here, we reviewed the dynamic alterations of B cells and their novel roles in animal models and patients with sepsis, and provided new perspectives for therapeutic strategies targeting B cells in sepsis.